E-learning quality: Social constructions and conceptions of Chilean teachers about online programs - Espejo Aubá, Paola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This qualitative study’s objective is to know the social constructions and conceptions of Chilean higher education teachers regarding the quality of e-learning programs. It is constituted by 30 in-depth interviews to university and professional institute professors, whose answers were analyzed under the theory of social constructions and the notion of conception as a mental image, to then be coded and categorized. The final objective of this investigation is to replicate the methodology in higher education students and employers, to contrast the results and establish a quality model.